Review paperOxidative stress – assassin behind the ischemic stroke - Pradeep, Hanumanthappa; Diya, Joseph B.; Shashikumar, Shivaiah; Rajanikant, Golgodu K. (Folia Neuropathologica, 2012)
Ischemic stroke is the second leading cause of death and disability worldwide and is associated with significant clinical and socioeconomic implications, emphasizing the need for effective therapies. Several neuroprotective strategies have failed in clinical trials because of poor knowledge of the molecular processes flanked with ischemic stroke. Therefore, uncovering the molecular processes involved in ischemic brain injury is of critical importance. Therapeutic strategies for ischemic stroke remain ineffective, though rapid advances occur in understanding the pathophysiology of the disease. The oxidative stress is one such high-potential phenomenon, the precise role of which needs to be understood during ischemic events. Nevertheless, the studies carried out in preclinical models of ischemic stroke have pointed to the major role of oxidative stress in exacerbating the ischemic injury. Oxidative stress leading to cell death requires generation of free radicals through multiple mechanisms, such as respiratory inhibition, Ca2+ imbalance, excitotoxicity, reperfusion injury and inflammation. Free radicals are highly reactive to all the molecular targets: lipids, proteins and nucleic acids, modifying their chemical structure and generating oxidation-derived products. This review discusses molecular aspects of oxidative stress in ischemic stroke and catastrophes that set up as an aftermath of the trauma.